2011
DOI: 10.1016/j.jds.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and distribution of developmental anomalies in the permanent teeth of a Turkish orthodontic patient population

Abstract: Background/purpose: The aims of this study were to determine the frequency and distribution of developmental anomalies in the permanent teeth of a Turkish orthodontic patient population and determine the relationships between gender and dental anomalies. Materials and methods: A retrospective study was performed using pretreatment dental casts, panoramic radiographs, and intraoral photographs of 3165 Turkish orthodontic patients (1940 females and 1225 males) aged 9e25 years. These patients were analyzed for ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
43
3
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 28 publications
17
43
3
5
Order By: Relevance
“…This study found a significant prevalence of developmental dental anomalies in Brazilian orthodontic patients, with high prevalence in females, similar to the results found by other authors (5,6,13,19). Hypodontia was observed significantly more in women; other authors have also reported prevalence of microdontia in females, while hyperdontia and macrodontia were more frequent in males (13).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This study found a significant prevalence of developmental dental anomalies in Brazilian orthodontic patients, with high prevalence in females, similar to the results found by other authors (5,6,13,19). Hypodontia was observed significantly more in women; other authors have also reported prevalence of microdontia in females, while hyperdontia and macrodontia were more frequent in males (13).…”
Section: Discussionsupporting
confidence: 90%
“…The patients' age ranged from 7-42 years old, with most of the dental anomalies diagnosed between 11 and 20 years, and this result was similar to that found in the literature (5,13,19). The time of tooth formation may interfere with the diagnosis of each anomaly.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations